Hybridization and the spread of the apple maggot fly, Rhagoletis pomonella (Diptera: Tephritidae), in the northwestern United States. (13th August 2015) - Arcella, Tracy; Hood, Glen R.; Powell, Thomas H. Q.; Sim, Sheina B.; Yee, Wee L.; Schwarz, Dietmar; Egan, Scott P.; Goughnour, Robert B.; Smith, James J.; Feder, Jeffrey L.
Abstract Hybridization may be an important process interjecting variation into insect populations enabling host plant shifts and the origin of new economic pests. Here, we examine whether hybridization between the native snowberry‐infesting fruit fly Rhagoletis zephyria (Snow) and the introduced quarantine pest R. pomonella (Walsh) is occurring and may aid the spread of the latter into more arid commercial apple‐growing regions of central Washington state, USA. Results for 19 microsatellites implied hybridization occurring at a rate of 1.44% per generation between the species. However, there was no evidence for increased hybridization in central Washington. Allele frequencies for seven microsatellites in R. pomonella were more 'R. zephyria‐like' in central Washington, suggesting that genes conferring resistance to desiccation may be adaptively introgressing from R. zephyria. However, in only one case was the putatively introgressing allele from R. zephyria not found in R. pomonella in the eastern USA. Thus, many of the alleles changing in frequency may have been prestanding in the introduced R. pomonella population. The dynamics of hybridization are therefore complex and nuanced for R. pomonella, with various causes and factors, including introgression for a portion, but not all of the genome, potentially contributing to the pest insect's spread.